Molecular identification of Fusarium isolates associated with passion fruit in five locations from Valle del Cauca, Colombia. - Henao-Henao, Edwin David; Hernandez-Medina, Carlos Alberto; Salazar-González, Claudia; Velasco-Belalcazar, Martha Lucia; Gómez-López, Eyder Daniel (Agronomía Mesoamericana, 2018)
The passion fruit’s production in Colombia has shown great advances; however, phytosanitary diseases remain as issues in passion fruit production. This includes the pathogens that hinder the establishment and development of the crop, such as some species of the genus Fusarium, pathogen considered as an important one because of the economic losses that it generates. The objective of this work was to molecularly identificate the populations of Fusarium associated with passion fruit (Passiflora edulis). Between January and December 2015, an isolation of 35 samples based on different affected organs of the plant and from localities found in five municipalities was performed in Valle del Cauca, Colombia. Eight isolates were selected and purified in order to perform their DNA’s extraction and also an amplification of region TEF 1 alpha. The PCR products were sequenced and compared with the NCBI database and Fusarium ID. The results obtained by sequencing showed that the isolates belong to Fusarium incarnatum, Fusarium solani, and Fusarium proliferatum, the first species had a mayor occurrence in the tested samples. The analysis of phylogenetic relationships was achieved by using the 6 MEGA program, and by using the similarity coefficient nearest neighbor, which allowed to observe the variability among the evaluated isolates.